Genetic data of 22 autosomal STR loci in Khyber-Pakhtunkhwa, Balochistan and Gilgit Baltistan population of Pakistan using PowerPlex® fusion system. (November 2022) - Shafique, Muhammad; Sajid, Namra; Aziz, Yasir; Afzal, Muhammad; Shahzad, Muhammad; Shehzadi, Abida; Bashir, Saliha; Daud, Shakeela; Ali Shahid, Ahmad
Highlights: In this article we have provided, allelic data for 22 autosomal STRs, their frequencies, and the forensic statistical parameters of 601 unrelated healthy individuals from Pakhtuns, Balochi and Balti population of Pakistan. The most discriminatory locus was Penta E in all groups and allele 15 was most frequent at D22S1045 in Balti whereas allele 8 was common at TPOX in others. Furthermore, the population differentiation and phylogenetic relationship among Pakistani samples and other nationalities were analysed. Abstract: In this study we have provided forensic genetic data of 22 autosomal STRs for Pakhtun, Balochi and Balti population of Pakistan in total of 601 samples. Among these loci, Penta E was found the most discriminatory in all groups and allele 15 was observed most frequent at D22S1045 in Balti whereas in other two populations allele 8 was more common at TPOX. The combined power of discrimination, combined power of exclusion and the combined matching probability was calculated as 0.999999999999999999999999998385, 0.999999988089728 and 1.615 × 10 -27 respectively. Based on population differentiation test, significant differences were observed when compared with other populations however, phylogenetic analysis revealed close genetic associations among Pakistani Populations.